Synthesis of divalent ligands of beta-thio- and beta-N-galactopyranosides and related lactosides and their evaluation as substrates and inhibitors of Trypanosoma cruzi trans-sialidase - Cano, María Emilia (2014)
In this work we describe the synthesis of mono- and divalent β-N- and β-S-galactopyranosides and related lactosides built on sugar scaffolds and their evaluation as substrates and inhibitors of the Trypanosoma cruzi trans-sialidase (TcTS). This enzyme catalyzes the transfer of sialic acid from an oligosaccharidic donor in the host, to parasite βGalp terminal units and it has been demonstrated that it plays an important role in the infection. Herein, the enzyme was also tested as a tool for the chemoenzymatic synthesis of sialic acid containing glycoclusters. The transfer reaction of sialic acid was performed using a recombinant TcTS and 3?-sialyllactose as sialic acid donor, in the presence of the acceptor having βGalp non reducing ends. The products were analyzed by high performance anion exchange chromatography with pulse amperometric detection (HPAEC-PAD). The ability of the different S-linked and N-linked glycosides to inhibit the sialic acid transfer reaction from 3?-sialyllactose to the natural substrate N-acetyllactosamine, was also studied. Most of the substrates behaved as good acceptors and moderate competitive inhibitors. A di-N-lactoside showed to be the strongest competitive inhibitor among the compounds tested (70% inhibition at equimolar concentration). The usefulness of the enzymatic trans-sialylation for the preparation of sialylated ligands was assessed by performing a preparative sialylation of a divalent substrate, which afforded the monosialylated compound as main product, together with the disialylated glycocluster.